Synthesis and Crystal Structure of Two Nitro-Regioisomers of cis-4-(4-Methoxyphenyl)-3-Methyl-2-Phenyl-1,2,3,4-Tetrahydroquinoline - Romero Bohórquez, Arnold Rafael; Laboratorio de Química Orgánica y Biomolecular Escuela de Química Facultad de Ciencias Universidad Industrial de Santander (2013)
Objectives. To synthesize two nitro-regioisomers of the cis-4-(4-methoxyphenyl)-3-methyl-2-phenyl-1,2,3,4-tetrahydroquinoline and carry out its complete structural characterization using single crystal X-ray diffraction technique and other spectroscopic methods. Materials and methods. The purity of the products and the composition of the reaction mixtures were monitored by thin layer chromatography over Silufol UV254 chromatoplates (0.25 mm). Products were isolated and purified by column chromatography (SiO2) using petroleum ether/ethyl acetate. Substances were identified using nuclear magnetic resonance (NMR) and mass spectrometry (MS). X-ray diffraction data for crystal characterization, were collected using a Bruker AFC7S Mercury diffractometer with Mo-Kα radiation (λ = 0.71073 Å) at room temperature. Results. Two nitro-regioisomers of the cis-4-(4-methoxyphenyl)-3-methyl-2-phenyl-1,2,3,4-tetrahydroquinoline have been synthesized via the “one pot” thee-component imino Diels-Alder reaction catalyzed by BF3.OEt2. The structures of these regioisomers was confirmed by 1H NMR and 13C NMR studies and the crystal structure was studies using single crystal X-ray diffraction technique. Conclusions. An easy and efficient synthetic route was employed for the preparation of two nitro-regioisomers of the tetrahydroquinoline derivatives. The spectroscopy analyses (NMR, GC-MS and X-ray diffraction) showed a complete characterization and permit to establish the correct stereochemistry for the tetrahydroquinoline ring. The molecular packing for the 5-nitro regioisomer 4 was resulted by combinations of intermolecular hydrogen bond and van der Waals interactions, while 7-nitro regioisomer 3 possesses only intermolecular van der Waals interactions and N—H··· π interactions also occur.